2016
DOI: 10.1103/physreve.93.030301
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing algebraic connectivity in interconnected networks

Abstract: Algebraic connectivity, the second eigenvalue of the Laplacian matrix, is a measure of node and link connectivity on networks. When studying interconnected networks it is useful to consider a multiplex model, where the component networks operate together with interlayer links among them. In order to have a well-connected multilayer structure, it is necessary to optimally design these interlayer links considering realistic constraints. In this work, we solve the problem of finding an optimal weight distribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…by combining empirical neuroimaging data with a whole brain simulation of neuronal network activity, we observe a transition between two regimes of multi-layer network similarly as previously described in the network literature (Sahneh et al, 2015;Shakeri et al, 2015;Van Mieghem, 2016). The results suggest that the healthy human brain operates at the transition point between these regimes, allowing it to switch between two configurations, one in which different layers are independent and a second in which there is strong dependence between layers.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…by combining empirical neuroimaging data with a whole brain simulation of neuronal network activity, we observe a transition between two regimes of multi-layer network similarly as previously described in the network literature (Sahneh et al, 2015;Shakeri et al, 2015;Van Mieghem, 2016). The results suggest that the healthy human brain operates at the transition point between these regimes, allowing it to switch between two configurations, one in which different layers are independent and a second in which there is strong dependence between layers.…”
Section: Discussionsupporting
confidence: 79%
“…4b since the row and column sum of any Laplacian is zero, and the diagonal elements are equal to the absolute value of the sum over the columns (Van Mieghem, 2010). The rationale to investigate the Laplacian spectrum is the following: previous studies have shown that by analysing the behaviour of the eigenvalues of the block-Laplacian matrix, specifically the second smallest eigenvalue (algebraic connectivity 2 ), two regimes of multi-layer network behaviour can be identified, one in which network layers act independently, and the second in which network layers are coupled strongly (Gomez et al, 2013;Martín-Hernández et al, 2014;Sahneh et al, 2015;Shakeri et al, 2015).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In this regime, the network acts as a whole [24]. This finding enables new strategies to build networks maximising λ 2 , as applied in [26], and can be useful in clinical contexts. With this regard, Tewarie et al analysed the λ 2 from resting state MEG recordings (healthy subjects) and compared the empirical results to those obtained from a biophysical model [27].…”
Section: Introductionmentioning
confidence: 92%
“…In the study of interconnected networks, much attention has been devoted to the Laplacian operator [21][22][23][24][25][26][27][28]. The Laplacian matrix L of an undirected graph is defined as D − A, where A is the adjacency matrix (its generic element A ij = 1 if i and j are connected, and A ij = 0 otherwise) and D = diag(A |1 ) is the diagonal matrix of degrees (we use the bra-ket notation, hence |1 denotes the column vector with all entries equal to 1).…”
Section: Introductionmentioning
confidence: 99%